2008
DOI: 10.2193/2006-305
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Breeder Loss on Wolves

Abstract: Managers of recovering wolf (Canis lupus) populations require knowledge regarding the potential impacts caused by the loss of territorial, breeding wolves when devising plans that aim to balance population goals with human concerns. Although ecologists have studied wolves extensively, we lack an understanding of this phenomenon as published records are sparse. Therefore, we pooled data (n = 134 cases) on 148 territorial breeding wolves (75 M and 73 F) from our research and published accounts to assess the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
167
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 41 publications
4
167
0
2
Order By: Relevance
“…As a result of lethal control, wild canids typically have younger age structures, larger litter size, smaller pack size, higher emigration and higher non-cull mortality (Brainerd et al 2008;Wallach et al 2015). Following lethal control, profound changes to social dynamics have also been observed in other top predator groups (wolves : Haber 1996;Brainerd et al 2008;bears: Wielgus et al 2001;large cats: Cooley et al 2009) and these changes influence predator-prey dynamics (Wallach et al 2015).…”
Section: The Ecological Consequences Of Lethal Control Can Potentiallmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of lethal control, wild canids typically have younger age structures, larger litter size, smaller pack size, higher emigration and higher non-cull mortality (Brainerd et al 2008;Wallach et al 2015). Following lethal control, profound changes to social dynamics have also been observed in other top predator groups (wolves : Haber 1996;Brainerd et al 2008;bears: Wielgus et al 2001;large cats: Cooley et al 2009) and these changes influence predator-prey dynamics (Wallach et al 2015).…”
Section: The Ecological Consequences Of Lethal Control Can Potentiallmentioning
confidence: 99%
“…Following lethal control, profound changes to social dynamics have also been observed in other top predator groups (wolves : Haber 1996;Brainerd et al 2008;bears: Wielgus et al 2001;large cats: Cooley et al 2009) and these changes influence predator-prey dynamics (Wallach et al 2015). Social integrity, therefore, is a key consideration when evaluating the ecological influence of top predators, such as dingoes (Wallach et al 2015).…”
Section: The Ecological Consequences Of Lethal Control Can Potentiallmentioning
confidence: 99%
“…Heavy hunting pressure on wolves decreased the average size of social groups and led to lower natural survival for a variety of reasons (Haber, 1996). Specifi cally, a review of multiple studies showed that removal of breeding wolves, Canis lupus, led to decreased wolf packs or to the dissolution of packs, and that pup survival was higher in larger packs and was correlated with the presence of auxiliary nonbreeders (Brainerd et al, 2008). Heavy hunting pressure on cougar populations, Puma concolor, was correlated with increased immigration, reduced kitten survival, and reduced female population growth (Cooley et al, 2009).…”
Section: Extinction Risk and Potential For Recoverymentioning
confidence: 99%
“…Larger packs kill more ungulate prey than smaller packs but have less food available per pack member than smaller packs (Fritts and Mech 1981;Messier and Crête 1985;Ballard et al 1987;Messier 1987;Thurber and Peterson 1993;Dale et al 1995). Pack members ("auxiliaries") help feed the pups in larger packs thereby increasing pup survival (Brainerd et al 2008). Pack size and litter size in an increasing Wolf population with abundant prey in Minnesota were positively correlated, and litter size in a declining population at low prey density was inversely related to pack size (Harrington et al 1983).…”
Section: Litter Sizesmentioning
confidence: 99%